If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -4p = 5p + -1 Reorder the terms: 8 + -4p = -1 + 5p Solving 8 + -4p = -1 + 5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. 8 + -4p + -5p = -1 + 5p + -5p Combine like terms: -4p + -5p = -9p 8 + -9p = -1 + 5p + -5p Combine like terms: 5p + -5p = 0 8 + -9p = -1 + 0 8 + -9p = -1 Add '-8' to each side of the equation. 8 + -8 + -9p = -1 + -8 Combine like terms: 8 + -8 = 0 0 + -9p = -1 + -8 -9p = -1 + -8 Combine like terms: -1 + -8 = -9 -9p = -9 Divide each side by '-9'. p = 1 Simplifying p = 1
| X/4+3-17 | | 10(t-6)+4t=7(2+2)-13 | | t-110=-90 | | 7y*3y= | | 7m+4n-3m+7n= | | x/-19=-2 | | (7x+2)-(2x^2+6x+8)= | | 4*5=585 | | 2*3=290 | | (3x^2-7x+2)+(4x^2+5x+5)= | | 28-4x=156 | | 3j-(j-4)+3= | | y=arcsin(x+2) | | -12x=-70 | | 4x-7=3.8 | | 5x+4x=70 | | 6(x-3)-4x=32 | | 4(-3.4)+1/3=(-3.4)-5/2 | | 0.03x-0.4x=2.85 | | a+0.8=-0.8a+3.86 | | 28+4x=156 | | -10=8x-3 | | 4(x+2)-6x+4=-42 | | 2+x=58 | | (-a^2+2)-(a^2-4)+(6a^2-5a*3)= | | 5x+140= | | .7=.35 | | 4s-12=5s+15 | | (4x^2+9x-2)+(4x^2+4x+19)-(8x^2-14)= | | 3(2x-1)=3x+1/2 | | 8K+1-1=17 | | 3(12-x)+6x=10 |